Novel mutations in LTBP2 identified in familial cases of primary congenital glaucoma - Rauf, Bushra (Mol Vis, 2020)
PURPOSE: Primary congenital glaucoma (PCG) is a genetically heterogeneous disorder caused by developmental defects in the anterior chamber and trabecular meshwork. This disease is an important cause of childhood blindness. In this study, we aim to identify the genetic determinants of PCG in three consanguineous families of Pakistani descent. METHODS: Affected members of all three families underwent detailed ophthalmological examination including slit-lamp biomicroscopy. Blood samples were collected from affected and healthy members of all three families, and genomic DNA was extracted. Linkage analysis was performed for the known or reported loci of PCG to localize the disease interval, and logarithm of odds (LOD) scores were calculated. All protein-coding exons of the candidate gene, latent transforming growth factor-beta binding protein 2 (LTBP2), were bidirectionally sequenced to identify the disease-causing mutation. RESULTS: Short tandem repeat (STR) marker-based linkage analysis localized the critical interval to chromosome 14q with a maximum two-point LOD score of 2.86 (PKGL076), 2.8 (PKGL015), and 2.92 (PKGL042). Bidirectional Sanger sequencing of LTBP2 revealed three novel pathogenic variants, i.e., c.3028G>A (p.Asp1010Asn), c.3427delC (p.Gln1143Argfs*35), and c.5270G>A (p.Cys1757Tyr) in PKGL076, PKGL015, and PKGL042, respectively. All three mutations segregated with the disease phenotype in their respective families and were absent in 200 ethnically matched normal chromosomes. CONCLUSIONS: We identified three novel mutations, p.D1010N, p.Q1143Rfs*35, and p.C1757Y, in LTBP2 responsible for PCG.